Study of the SST turbulence model for the 2D NASA wall-mounted hump separated FLOW problem with plenum case - Madaliev Murodil; Abdulkhaev Zokhidjon; Kurpayanidi Konstantin; Abdullayev Alisher; Ilyosov Asrorjon (E3S Web of Conferences, 2024)
The article presents the results of the standard SST turbulence model in the Comsol Multiphysics 6.1 software package for 2D NASA wall-mounted hump separated flow with plenum case problems, which are presented in the NASA database. In this work, the finite element method is used for the numerical implementation of the turbulence equations. To stabilize the discretized equations, Galerkin least squares (GLS) stabilization and crosswind propagation stabilization were used. The results were taken for different computational grids. The results obtained are compared with the results of experimental data.